Intervista a Massimo Fagioli - Masini, Andrea; Fagioli, Massimo (Il sogno della farfalla, 2025)
In this interview, the psychiatrist of Collective Analysis briefly reflects on his experience as director of the therapeutic community for psychotic patients at the Bellevue Clinic in Kreuzlingen in 1963. He recounts the unique features of the experience, particularly in terms of direct psychotherapeutic relationships, and situates it within the context of his previous and subsequent work. In doing so, he sketches a vivid and coherent picture of the early stages of his original research on the unconscious mind, which would later lead to his writings of the volume Death instinct and knowledge.